High CD90 Expression is A Predictor of Axillary Nodal Metastasis in Breast Carcinoma - Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra; Wetan, Ni Gusti Ayu Agung Manik Yuniawaty (Indonesian Journal of Cancer, 2024)
Background: Metastasis is the most common cause of death in breast cancer and nodal metastasis is one of the most important predictive factors for distance metastasis. One of the intrinsic properties of cancer cells is that they resemble stem cells which are capable of self-renewal, resistance to chemotherapy and radiation, and metastasis. CD90 is a stem cell marker found in several malignancies, including breast carcinoma. The objective of this study was to prove that CD90 can predict the occurrence of axillary nodal metastasis in breast carcinoma. Methods: The study design was a case-control study. The subjects of this study were breast cancer patients at Prof. Dr. I. G. N. G. Ngoerah Hospital who underwent mastectomy and axillary lymphadenectomy in the year 2019. CD90 immunohistochemistry was performed and its association with metastasis, along with various clinicopathological markers, was assessed with chi-square and logistic regression tests with a significance level determined at α=0.05. Results: There were 25 cases of breast carcinoma with axillary nodal metastasis and 25 cases without metastasis. There was a significant relationship between high CD90 expression and the occurrence of nodal metastasis (p=0.010). There was no relationship between patient age, histologic grade, histologic subtype, molecular subtype, and T-stage with axillary nodal metastasis. Breast carcinoma patients with high CD90 expression have a 7.25 times higher nodal metastasis risk compared to patients with low CD90 expression. Conclusion: High CD90 expression could predict axillary nodal metastasis in breast carcinoma.